The culture shock for foreign speakers in Indonesia - Muzaki, Helmi; Susanto, Gatut; Widyartono, Didin; Himawan, Riswanda; Wodajo, Mengesha Robso; Gandonu, Peter (Universitas Mulawarman, 2025)
Culture shock is a crucial problem for foreign students, especially foreign speakers coming to Indonesia to learn Indonesian. Culture shock has a negative impact on a person's psychology and health. Culture shock cannot be avoided, but its impact can be reduced by understanding the culture of the target area. This research aims to describe the culture shock experienced by foreign speakers. The method in this research is qualitative descriptive. The data source for this research was 33 respondents from 16 countries who had experienced culture shock. The data analysis stage in this research was carried out in 3 stages: data condensation, data display, and conclusion or verification. This research shows that there are cultural shocks, including ways of interacting with other people, food, discipline, cleanliness, Profession, transportation, and language. The culture shock experienced by foreign speakers varies depending on their region of origin. The main cause of culture shock is the differences in geographic location and the beliefs held by these communities.